2021
DOI: 10.3389/fpsyg.2021.672980
|View full text |Cite
|
Sign up to set email alerts
|

A Sound Prediction: EEG-Based Neural Synchrony Predicts Online Music Streams

Abstract: Neuroforecasting predicts population-wide choices based on neural data of individuals and can be used, for example, in neuromarketing to estimate campaign successes. To deliver true value, the brain activity metrics should deliver predictive value above and beyond traditional stated preferences. Evidence from movie trailer research has proposed neural synchrony, which compares the similarity of brain responses across participants and has shown to be a promising tool in neuroforecasting for movie popularity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…In our study, participants who exhibited high ISC during listening to the healthy eating call might have memorized more information contained in it, which might have increased their compliance with the expert. Overall, neural synchrony is a promising tool in neuroforecasting for movie and music popularity (Christoforou et al, 2017 ; Leeuwis et al, 2021 ), as well as for television ads (Dmochowski et al, 2014 ). Here, we show that neural synchrony may, in addition, be a promising tool in neuroforecasting of healthy eating advertisements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, participants who exhibited high ISC during listening to the healthy eating call might have memorized more information contained in it, which might have increased their compliance with the expert. Overall, neural synchrony is a promising tool in neuroforecasting for movie and music popularity (Christoforou et al, 2017 ; Leeuwis et al, 2021 ), as well as for television ads (Dmochowski et al, 2014 ). Here, we show that neural synchrony may, in addition, be a promising tool in neuroforecasting of healthy eating advertisements.…”
Section: Discussionmentioning
confidence: 99%
“…An EEG-derived measure that is being increasingly used in this research area is the similarity of individuals’ neural activity, or intersubject correlation (ISC). As a marker of engagement and attention (Hasson et al, 2004 ; Dmochowski et al, 2012 ; Ki et al, 2016 ), ISC has successfully been used to predict population-wide music popularity (Leeuwis et al, 2021 ), movies’ box-office performance (Christoforou et al, 2017 ) and individual preferences for television ads (Dmochowski et al, 2014 ). Given these findings, ISC is considered to be a promising neurophysiological measure of advertising effectiveness in social contexts (Pozharliev et al, 2017 ), especially when the study designs include long-duration stimuli (Hakim and Levy, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Garczarek-Bąk et al [ 115 ] evaluated the predictive power of their model for private label purchasing using the Chi-square test. Different studies utilized Levene’s and Shapiro–Wilk’s tests to verify whether or not their samples fit normal distributions [ 104 , 112 ]. Apart from these, descriptive statistics such as mean, median, and standard deviation were used by some studies to interpret the data [ 53 , 54 , 87 ].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Finally, ISC may contribute not only basic scientific findings but also predictive insights for real-world application (Kaneshiro & Dmochowski, 2015). Leeuwis et al (2021) showed that EEG alpha power synchrony could predict song popularity based on Spotify 8 streams, when subjective ratings from the experimental sample could not. Small-sample EEG ISC has also been used to predict population-level preferences for television commercials and in a time-resolved fashion over a television episode (Dmochowski et al, 2014).…”
Section: Future Workmentioning
confidence: 99%